Solid-state reactions of mercury with pure noble metals - Part 2. Mercury-iridium system - Fertonani, F. L.; Milare, E.; Benedetti, Assis Vicente [UNESP]; Ionashiro, Massao [UNESP] (Springer, 2002)
Thermogravimetry, cyclic voltammetry and other analytical techniques were used to study the reactions of mercury with pure iridium. The results allowed to suggest when subjected to heat or anodic stripping voltammetry an electrodeposited mercury film reacts with Ir substrate and at least three mass loss steps and three peaks appear in the mercury desorption process. The first two were attributed to Hg(0) species removal like a mercury bulk and a mercury monolayer. The last can be ascribed to the mercury removal from a solid solution with iridium.
Keywords: cyclic voltammetry; iridium; mercury; SEM; TG; X-ray diffraction